Das Zahlenbuch 4. Förderheft - Häsel-Weide, Uta; Nührenbörger, M.; Reinold, M.

Das Zahlenbuch. Förderkommentar Lernen zum 4. Schuljahr - Häsel-Weide, Uta; Nührenbörger, M.; Reinold, M.

Lernumgebungen für den inklusiven Mathematikunterricht zwischen reichhaltiger Offenheit und fokussierter Förderung - Häsel-Weide, Uta (Zwischen Persönlichkeitsbildung und Leistungsentwicklung. Fachspezifische Zugänge zu inklusivem Unterricht)

Understanding Artificial Intelligence – A Project for the Development of Comprehensive Teaching Material - Schlichtig, Michael; Opel, Simone Anna; Budde, Lea; Schulte, Carsten (ISSEP 2019 - 12th International conference on informatics in schools: Situation, evaluation and perspectives, Local Proceedings)
Artificial intelligence (AI) has the potential for far-reaching – in our opinion – irreversible changes. They range from effects on the individual and society to new societal and social issues. The question arises as to how students can learn the basic functioning of AI systems, what areas of life and society are affected by these and – most important – how their own lives are affected by these changes. Therefore, we are developing and evaluating school materials for the German ”Science Year AI”. It can be used for students of all school types from the seventh grade upwards and will be distributed to about 2000 schools in autumn with the support of the Federal Ministry of Education and Research. The material deals with the following aspects of AI: Discussing everyday experiences with AI, how does machine learning work, historical development of AI concepts, difference between man and machine, future distribution of roles between man and machine, in which AI world do we want to live and how much AI would we like to have in our lives. Through an accompanying evaluation, high quality of the technical content and didactic preparation is achieved in order to guarantee the long-term applicability in the teaching context in the different age groups and school types. In this paper, we describe the current state of the material development, the challenges arising, and the results of tests with different classes to date. We also present first ideas for evaluating the results.
Keywords: Artificial Intelligence; Machine Learning; Teaching Material; Societal Aspects; Ethics. Social Aspects; Science Year; Simulation Game

Entwicklung und Reflexion einer Unterrichtssequenz zum Maschinellen Lernen als Aspekt von Data Science in der Sekundarstufe II - Opel, Simone Anna; Schlichtig, Michael; Schulte, Carsten; Biehler, Rolf; Frischemeier, Daniel; Podworny, Susanne; Wassong, Thomas (INFOS)

Maschinelles Lernen im Unterricht mit Jupyter Notebook - Schlichtig, Michael; Opel, Simone Anna; Schulte, Carsten; Biehler, Rolf; Frischemeier, Daniel; Podworny, Susanne; Wassong, Thomas (INFOS)

Developing Teaching Materials on Artificial Intelligence by Using a Simulation Game (Work in Progress) - Opel, Simone Anna; Schlichtig, Michael; Schulte, Carsten (WiPSCE)

Global generalized solutions to a parabolic-elliptic Keller-Segel system with singular sensitivity - Black, Tobias (Discrete & Continuous Dynamical Systems - S)
Keywords: Applied Mathematics; Discrete Mathematics and Combinatorics; Analysis

The Stokes Limit in a Three-Dimensional Chemotaxis-Navier–Stokes System - Black, Tobias (Journal of Mathematical Fluid Mechanics)
Keywords: Applied Mathematics; Computational Mathematics; Condensed Matter Physics; Mathematical Physics

A Keller‐Segel‐fluid system with singular sensitivity: Generalized solutions - Black, Tobias; Lankeit, Johannes; Mizukami, Masaaki (Mathematical Methods in the Applied Sciences)
Keywords: General Engineering; General Mathematics

Stabilization in the Keller–Segel system with signal-dependent sensitivity - Black, Tobias; Lankeit, Johannes; Mizukami, Masaaki (Applicable Analysis)
Keywords: Applied Mathematics; Analysis

Octave-Band Microwave Frequency Synthesizer Using Mode-Locked Laser as a Reference - Bahmanian, Meysam; Tiedau, Johannes; Silberhorn, Christine; Scheytt, Christoph (2019 International Topical Meeting on Microwave Photonics (MWP))
An octave-band voltage-controlled oscillator is phase-locked on the envelope of the pulse train from a mode-locked laser. The locking scheme employs a balanced Mach-Zehnder modulator with two photodiodes as a phase detector. The phase.locked loop has a loop bandwidth of approximately 1MHz and an in-band phase noise of approximately -135dBc/Hz at all frequencies. The integrated jitter from 1kHz to 100MHz is 21fs, 18.3fs and 13.8fs at 5.016GHz, 7.6GHz and 10.032GHz carrier frequencies, respectively. To the authors' knowledge, this is the best jitter performance reported for a PLL with MZM-based phase detection and the first reported PLL of this type featuring an octave-band frequency range.

Unraveling the Search Space of Abusive Language in Wikipedia with Dynamic Lexicon Acquisition - Chen, Wei-Fan; Al-Khatib, Khalid; Hagen, Matthias; Wachsmuth, Henning; Stein, Benno (Proceedings of the Second Workshop on Natural Language Processing for Internet Freedom)

A Hybrid Space Compactor for Adaptive X-Handling - Maaz, Mohammad Urf; Sprenger, Alexander; Hellebrand, Sybille (50th IEEE International Test Conference (ITC))
The test for small delay faults is of major importance for predicting potential early life failures or wearout problems. Typically, a faster-than-at-speed test (FAST) with sev¬eral different frequencies is used to detect also hidden small delays, which can only be propagated over short paths. But then the outputs at the end of long paths may no longer reach their stable values at the nominal observation time and must be considered as unknown (X-values). Thus, test response compaction for FAST must be extremely flexible to cope with high X-rates, which also vary with the test frequencies. Stochastic compaction introduced by Mitra et al. is controlled by weighted pseudo-random signals allowing for easy adaptation to varying conditions. As demonstrated in previous work, the pseudo-random control can be optimized for high fault efficiency or X-reduction, but a given target in fault efficiency cannot be guaranteed. To close this gap, a hybrid space compactor is introduced in this paper. It is based on the observation that many faults are lost in the compaction of relatively few critical test patterns. For these critical patterns a deterministic compaction phase is added to the test, where the existing compactor structure is re-used, but controlled by specifically determined control vectors.
Keywords: Faster-than-at-speed test; BIST; DFT; Test response compaction; Stochastic compactor; X-handling

Improved fractal Weyl bounds for hyperbolic manifolds. With an appendix by David Borthwick, Semyon Dyatlov and Tobias Weich - Dyatlov, Semyon; Borthwick, David; Weich, Tobias (Journal of the European Mathematical Society)
Keywords: Applied Mathematics; General Mathematics

Rezension: Klaus Volkert: In höheren Räumen – Der Weg der Geometrie in die vierte Dimension - Hoffmann, Max (Mathematische Semesterberichte)

Spectral Asymptotics for Kinetic Brownian Motion on Hyperbolic Surfaces - Kolb, Martin; Weich, Tobias; Wolf, Lasse Lennart (arXiv:1909.06183)
The kinetic Brownian motion on the sphere bundle of a Riemannian manifold $M$ is a stochastic process that models a random perturbation of the geodesic flow. If $M$ is a orientable compact constant negatively curved surface, we show that in the limit of infinitely large perturbation the $L^2$-spectrum of the infinitesimal generator of a time rescaled version of the process converges to the Laplace spectrum of the base manifold. In addition, we give explicit error estimates for the convergence to equilibrium. The proofs are based on noncommutative harmonic analysis of $SL_2(\mathbb{R})$.

A DC bias approach to the characterisation of non-linear material parameters of piezoelectric ceramics - Dreiling, Dmitrij; Feldmann, Nadine; Henning, Bernd
Keywords: piezoelectric materials; piezoelectric properties; DC bias field; non-linear material parameters

Arbitrary sensitivity for inverse problems in piezoelectricity - Jurgelucks, Benjamin; Schulze, Veronika; Feldmann, Nadine; Claes, Leander

Stochastic Spikes and Poisson Approximation of One-Dimensional Stochastic Differential Equations with Applications to Continuously Measured Quantum Systems - Kolb, Martin; Liesenfeld, Matthias (Annales Henri Poincaré)
Motivated by the recent contribution (Bauer and Bernard in Annales Henri Poincaré 19:653–693, 2018), we study the scaling limit behavior of a class of one-dimensional stochastic differential equations which has a unique attracting point subject to a small additional repulsive perturbation. Problems of this type appear in the analysis of continuously monitored quantum systems. We extend the results of Bauer and Bernard (Annales Henri Poincaré 19:653–693, 2018) and prove a general result concerning the convergence to a homogeneous Poisson process using only classical probabilistic tools.